Moctezuma and the Aztecs - Burrell, Roy E. C.; McBride, Angus (Austin, Tex. Raintree/Steck-Vaughn, 1993)
Traces the history of the Aztec Indians, describing their religion, social structure, daily life, and the consequences of their contact with the Spanish during the reign of Moctezuma II.
"A Mirabel book"--T.p. verso.
Includes index.
Grade level : 4 - 6
Keywords: Aztecs -- Juvenile literature; Aztecs; Indians of Mexico